Telomere length, telomerase expression, and oxidative stress in lead smelters. (December 2016) - Pawlas, Natalia; Płachetka, Anna; Kozłowska, Agnieszka; Mikołajczyk, Agnieszka; Kasperczyk, Aleksandra; Dobrakowski, Michał; Kasperczyk, Sławomir
The negative health effects caused by lead (Pb) exposure are widely recognized; however, the molecular mechanisms remain unknown. The aim of this study was to assess the effect of occupational Pb exposure on telomere length and to investigate the potential mechanisms leading to telomere shortening. A cohort of 334 male Pb smelters (exposed group) and 60 age-adjusted males unexposed to Pb (control group) were examined. Assessments of relative telomere length (rTL) and telomerase reverse transcriptase (TERT) gene expression were performed using quantitative real-time polymerase chain reactions. Assessments of whole blood Pb (B-Pb) and whole blood cadmium (B-Cd) concentrations and serum selenium concentration (S-Se) were performed using graphite furnace atomic absorption spectrometry. We analyzed total oxidation status (TOS), lipid hydroperoxides (LHPs), malonylodialdehyde levels in serum (MDA) and in erythrocyte hemolysates (MDA-hgb), and 8-hydroxy-deoxy-guanosine (8-OHdG). The Pb-exposed group had higher B-Pb values and shorter rTL than the control group. The arithmetic mean values calculated for B-Pb were 33 µg/dL versus 2.2 µg/dL ( p < 0.0001), and the rTL values were 0.928 and 1.126 relative units ( p = 0.001), respectively, for the Pb-exposed and control groups. The rTL was found to gradually shorten in response to the increasing levels of Pb exposure. The Pb-exposed group also demonstrated a higher level of oxidative stress than the control group, which was indicated by increased TOS and MDA-hgb values. rTL was negatively associated with parameters that indicated increased oxidative stress, including TOS (Spearman's rank coefficient ( r S ) = −0.16; p < 0.01) and MDA-hgb ( r S = −0.17; p < 0.001). No correlations were found between rTL and B-Cd and S-Se or smoking and MDA and LHP levels. Univariate analysis indicated that B-Pb was associated with decreased rTL ( β =−0.0041; p = 0.0063) and that the association between B-Pb and rTL remained significant, even when adjusting for age ( β = −0.0041; p = 0.0065) and in multivariable-adjusted model ( β = −0.0042; p = 0.0063). In conclusion, occupational Pb exposure resulted in decreased rTL and may represent a mechanism that contributes to Pb-related diseases.